3D printed coil array for spherical harmonic spatial encoding in magnetic particle imaging (Transactions on Additive Manufacturing Meets Medicine, 2025)
Magnetic particle imaging is a promising method of noninvasive diagnostics that is being consistently developed for future implementation in clinical routine. The method is based on measuring the magnetic response of superparamagnetic nanoparticles using a set of drive, gradient, and receive coils. One of the major technical obstacles to translating the method to the human scale is the large amount of energy required to establish gradient fields of sufficient levels. In this work, we propose a novel approach to spatial encoding of the volumetric distribution of superparamagnetic nanoparticles by using only a drive field and an array of receive coils. The coils have a complex structure designed using numerical optimization algorithms, and only additive manufacturing methods provide the necessary freedom to translate this concept into the working prototype we demonstrate.
Keywords: MPI; Spherical harmonics; Imaging; Spatial encoding; Magnetic fields; Nanoparticles